Application of augmented reality and surgical robotic navigation in total hip and knee replacement - Zhang, Xiuli; Liu, Yong; Luo, Wen; Guo, Yansu (Frontiers in Surgery, 2025)
With advancements in computer vision, artificial intelligence, and other cutting-edge science and technologies, the focus of modern surgical technology has increasingly shifted towards intelligent, digital, minimally invasive, and precision approaches. Augmented reality (AR) technology and surgical robotics have emerged as significant research areas in total hip and knee replacement. Navigation systems, which are pivotal in both AR and robotic surgery, play a crucial role in guiding surgical operations using shared techniques. Recent developments in navigation systems for hip and knee replacement have focused on more natural, intelligent, and efficient methodologies. The use of AR and surgical robots for navigation has significantly enhanced the safety and accuracy of these procedures. Importantly, these technologies eliminate the need to implant positioning screws or other reference objects into the bone structure, thereby markedly reducing the risk of severe complications, such as lower limb pain and fractures. This study reviews the current applications, main challenges, and solutions associated with AR and surgical robot navigation systems for total hip and knee replacements.